“Se morre, se mata”: um estudo sociológico sobre saúde mental e suicídio na PMESP - Coelho, Thiago (Universidade Federal de São Carlos, 2025)
The issue of mental health, especially in relation to suicide, is highly complex in terms of its causes and means, which makes it difficult to create and maintain public policies aimed at preventing it, especially in the area of Public Security. This project aimed to analyze the actions of the Military Police of the State of São Paulo regarding mental health care and suicide prevention between 2020, 2021, and 2022. The legislative text of the Mental Health System and academic production related to the topic were analyzed to understand its functioning. In addition, secondary data on suicide among military police officers were collected, focusing on the southeast region. A booklet proposed by the institution for suicide prevention among military police officers was also analyzed. Finally, data were requested via the Access to Information Law regarding the total number of users of SiSMen and the Suicide Prevention Program, through stratification by gender, ethnicity, and rank. Additionally, data was requested on the psychologists working in the PMESP and how many of these are military police officers performing this function. A mixed methodology was used to collect the data. It was concluded that institutions still have low adherence to the dissemination of data on suicide, using information from previous and, in some cases, unofficial collections. Furthermore, a contradiction of austerity and care was observed, which, even though SiSMen is structured at the bureaucratic level, can be related to the coexistence of the idea that normalizes discipline and hierarchy, permeating the content of psychological vulnerability on the part of military police officers.
"To die and to kill": a sociological study about mental health and suicide on Military Police of Sao Paulo
Keywords: Sociologia da polícia; Saúde mental; Polícia Militar; Trabalho policial; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS